Accommodating New Modes of Work in the Era of the Fourth Industrial Revolution in Ghana: Some Comparative Lessons from the United Kingdom and South Africa - Coleman, Theophilus Edwin; Mpedi, Letlhokwa George (Comparative and International Law Journal of Southern Africa)
Over the past decade, Ghana has significantly improved in the digitalisation and transformation agenda. The digitalisation agenda has paved the way for creating an inclusive digital economy. Through this agenda, many Ghanaians now have access to digital platforms, particularly those in the financial and transportation sectors. The quest to digitalise the Ghanaian economy has also created an enabling platform for digital entrepreneurship. The digital economy ecosystem has presented many Ghanaians with economic and employment opportunities that did not exist in the traditional or mainstream economy. While the economic potential of the Ghanaian digital economy cannot be denied, the employment opportunities created by the digital transformation drive present some challenges for the traditional labour market. Moreover, the novel nature of the digital transformation drive poses some difficulties for the existing legal framework of labour laws in Ghana. In addition to examining how Ghana’s labour laws can accommodate gig workers, this article discusses the digital economy’s meaning and significance in Africa, particularly in Ghana. Furthermore, it discusses the new modes of work associated with the digital economy. In addressing the issue of whether the current legal framework in Ghana can accommodate gig workers, the article reflects on the nature of the relationship between gig workers and owners of digital platforms. The article accordingly deals with the issue of whether the Labour Act 651 of 2003 offers guidance in addressing the employment status of gig workers in Ghana. In dealing with whether gig workers are employees of digital platform providers, this article draws some comparative and judicial lessons from the legal position in the United Kingdom (UK) and South Africa. The article concludes with a call for the statutory protection of gig workers in Ghana.